The association of vitamin D insufficiency with the prevalence of obesity in children: implications for serum calcium levels, alkaline phosphatase activity, and bone maturation - Xu, Yue; Song, Lingyun; Zhou, Li (Frontiers in Nutrition, 2024)
Background: Vitamin D deficiency has been identified as a potential risk factor for various adverse health outcomes. However, its specific role in metabolic regulation and skeletal development in school-aged children is not fully understood. This study aimed to explore the correlation between vitamin D deficiency and childhood obesity rates, and its impact on serum calcium, alkaline phosphatase, and bone age in children. Methods: The study analyzed clinical data from 159 school-aged children who underwent medical examinations. Participants were divided into the 25-hydroxyvitamin D3 (25(OH)D3) deficiency group and the 25(OH)D3 normal group based on their serum levels. We compared body mass index (BMI), total cholesterol (TC), triglycerides (TG), Ca, ALP, bone age, fasting blood glucose (FBG), and hemoglobin A1c (HbA1c) between the two groups. Logistic regression and Spearman correlation analyses were performed to further investigate relationships between 25(OH)D3 levels and metabolic and bone-related markers. Results: This study showed that the 25(OH)D3 deficiency cohort exhibited significantly higher BMI, TC, TG, and ALP levels, with lower Ca levels and delayed bone age compared to the normal group. Logistic regression analysis identified Ca, ALP, and bone age as significant predictors of 25(OH)D3 deficiency. Subgroup analysis showed that in the 25(OH)D3 deficient group, children with higher BMI had elevated TC, ALP levels, and delayed bone age, while Ca levels were lower. Correlation analysis confirmed the predictive value of these markers for 25(OH)D3 deficiency. Conclusion: Our findings demonstrate that 25(OH)D3 deficiency is strongly associated with obesity in school-aged children and may negatively affect normal skeletal development. Regular monitoring of 25(OH)D3 levels in school-aged children is essential for ensuring proper growth and development, especially in those at risk for obesity.